Queens of Bombus diversus tersatus (Hymenoptera: Apidae) are innately attracted to floral scents emitted by Cremastra appendiculata (Orchidaceae). Issue 3 (23rd February 2017) - Kubo, Ryohei; Ono, Masato
Abstract: The rewarding orchid, Cremastra appendiculata (Orchidaceae), has a strong floral scent and is pollinated by long-tongued bumble bee queens ( Bombus diversus tersatus Smith; Hymenoptera: Apidae). The response of queens of B. diversus tersatus to the scent of C. appendiculata was investigated using a gas chromatography–electroantennographic detector system and Y-tube olfactometer. Gas chromatography–electroantennographic detector analysis of flower extracts showed that seven compounds (nerol, methyl decanoate, methyl dodecanoate, methyl tetradecanoate, methyl hexadecanoate, ethyl dodecanoate, and ethyl tetradecanoate) elicited antennal responses from B. diversus tersatus queens. Further, Y-tube olfactometer test results showed that queens significantly preferred both the flower extracts and synthetic mixture of seven EAD active compounds compared with pentane (a solvent control). These results suggest that floral scents play an important role in attracting queens and promote successful pollination.